Vector mechanics for engineers [electronic resource] : statics - Beer, Ferdinand Pierre, 1915-2003; Johnston, Russell (Elwood Russell), 1925-; Eisenberg, Elliot R. (New York, NY : McGraw-Hill/Higher Education, 2007)
05